Strategi Rumah Sakit dalam Menghadapi Perubahan Perilaku Pelanggan di Masa Pandemi Covid-19 - Natasya Pribadi (Yayasan Pendidikan Medika Indonesia, 2023)
The COVID-19 pandemic has caused changes in customer behavior of getting health services in health facilities. During the pandemic, many customers have chosen to use digital health services. The purpose of this study is to determine the most effective hospital strategy in facing customer behavior changes due to COVID-19 pandemic. This research method is taking secondary data of number of patient visits to X hospital before and after pandemic, then analyzing and present it in a comprehensive narrative form. From the research results, it was found that the COVID-19 pandemic caused restlessness in the community which was in line with decrease of number of outpatient visits at X hospital so it was necessary to find the most effective strategy in dealing with changes in customer behavior in the era of the COVID-19 pandemic by changing the marketing method to digital marketing and maximizing online health promotion media such as advertisements in electronic media which aims to streamline the increased operational costs due to new standard procedures in securing the hospital environment, both for employees and other medical personnel, especially in order to face uncertainties in the future.